Programas de erradicação, reassentamento e urbanização das favelas: Delhi e Mumbai - Dupont, Véronique; Saglio-Yatzimirsky, Marie-Caroline (Estudos Avançados, 2009)
This comparative article focuses on public policies regarding slums in the two largest Indian metropolises, Delhi, the political capital, and Mumbai, the foremost economic hub, which face different geomorphologic constraints. It highlights the similar trends and the divergences in slum polices implemented since the 1950's: environmental improvement, resettlement and in situ rehabilitation. The explanation of the main differences lies in distinctive interplays of actors: public, private and civil society.